2001
DOI: 10.1128/jb.183.19.5733-5742.2001
|View full text |Cite
|
Sign up to set email alerts
|

SdiA of Salmonella enterica Is a LuxR Homolog That Detects Mixed Microbial Communities

Abstract: Proteins of the LuxR family detect the presence of N-acylhomoserine lactones (AHLs) and regulate transcription accordingly. When AHLs are synthesized by the same species that detects them, the system allows a bacterium to measure the population density of its own species, a phenomenon known as quorum sensing. The sdiA genes of Escherichia coli and Salmonella enterica serovar Typhimurium are predicted to encode LuxR homologs. However, these species do not appear to synthesize AHLs or any other molecule detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
293
1
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(313 citation statements)
references
References 58 publications
14
293
1
1
Order By: Relevance
“…Both these bacteria are not reported to produce AHLs. As mentioned before, SdiA has been proposed to function in interspecies signaling and this is due to the observations that it binds to more than one type of AHL molecule and regulates target genes in an AHL dependent manner (Michael et al, 2001;Smith and Ahmer, 2003;Yao et al, 2006). SdiA also functions in mediating the effects of indole, a stationary phase signaling molecule of E. coli that may also serve as an interspecies signal as its levels can be changed by other bacteria in a mixed community .…”
Section: Ahl Response By Unpaired Quorum Sensing Luxr-family Proteinsmentioning
confidence: 99%
“…Both these bacteria are not reported to produce AHLs. As mentioned before, SdiA has been proposed to function in interspecies signaling and this is due to the observations that it binds to more than one type of AHL molecule and regulates target genes in an AHL dependent manner (Michael et al, 2001;Smith and Ahmer, 2003;Yao et al, 2006). SdiA also functions in mediating the effects of indole, a stationary phase signaling molecule of E. coli that may also serve as an interspecies signal as its levels can be changed by other bacteria in a mixed community .…”
Section: Ahl Response By Unpaired Quorum Sensing Luxr-family Proteinsmentioning
confidence: 99%
“…AHLs: C6-N-hexanoyl homoserine lactone, C8-N-octanoyl homoserine lactone, C10-N-decanoyl homoserine lactone, and C12-N-dodecanoyl homoserine lactone. Michael et al (2001) showed that, depending on the AHL assessed, a concentration of 1 nM suffices to induce sdiA gene expression in Salmonella Typhimurium. Confirmation that a 100 nM concentration of different AHLs does not negatively affect the microorganism's growth is essential for studying phenotypes regulated by these AIs because it enables the detection of phenotypes stimulated by this signal.…”
Section: Quorum Sensing In Salmonella Enteritidis Pt4 578mentioning
confidence: 99%
“…However, SdiA can detect and bind AHLs produced by others bacterial species (Michael et al, 2001). SdiA is a LuxR homologue and has two functional domains.…”
Section: Rck Regulationmentioning
confidence: 99%
“…A genetic screening performed in S. Typhimurium to identify genes regulated by SdiA (suppressor of d ivision inhibition), a transcriptional regulator of quorum sensing, has suggested that rck belongs to a putative operon called the "rck operon" whose expression is activated by SdiA in an Acyl Homoserine Lactone (AHLs)-dependent manner (Figure 6) (Ahmer et al, 1998;Michael et al, 2001). …”
Section: Rck Regulationmentioning
confidence: 99%